About syntactic derivation among stable word combination - Golubeva, Victoria K. (Journal of the Belarusian State University. Philology, 2023)
The article considers the possibility of transforming stable word combinations with structure adjective + noun into the construction abstract noun + genitive. Phraseologisms (collocations and idioms) and two-word terms are considered among stable combinations. It is revealed whether the identity of the referent situation, which is indicated by the original phrase, is preserved during such a transformation. Considering the transformational potential of the original phrases, non-transformable and transformable constructions are distinguished, and among the transformable ones, correlative (retain the semantic correspondence of the original construction) and non-correlative (form a new meaning). The formal and semantic factors preventing transformation and promoting it are investigated.
Keywords: syntactic derivation; abstract noun; referent; idiom; collocation; phraseologism; terminological combination